Jacob of Edessa and the Syriac culture of his day - Haar Romeny, R. B. ter. (Monographs of the Peshitta Institute, 2008)
Jacob of Edessa (c.640-708) is considered the most learned Christian of the early days of Islam. In all fifteen contributions to this volume, written by prominent specialists, the interaction between Christianity, Judaism, and the new religion is an important issue. The articles discuss Jacob's biography as well as his position in early Islamic Edessa, and give a full picture of the various aspects of Jacob of Edessa's life and work as a scholar and clergyman. Attention is paid to his efforts in the fields of historiography, correspondence, canon law, text and interpretation of the Bible, language and translation, theology, philosophy, and science. The book, which marks the 1300th anniversary of Jacob's death, also contains a bibliographical clavis.